A Postmortem Histological Study on Percentage Volume of Parenchyma and Stroma of the Human Parathyroid Glands - Mahbub, Sabiha; Nurunnabi, Abu Sadat Mohammad; Ara, Shamim; Alim, Abdul (Anwer Khan Modern Medical College Journal, 2014)
A cross-sectional descriptive study was performed in the Department of Anatomy, Dhaka Medical College, Dhaka, from January to December 2008, on post mortem parathyroid glands of 60 Bangladeshi people in different age groups. A total of 207 parathyroid glands were identified in relation to posterior border of thyroid lobes and collected from those 60 cadavers. The samples were collected from the unclaimed dead bodies within 24 hours after death that were under examination in the Department of Forensic Medicine of Dhaka Medical College, Dhaka. The samples were divided into three different age groups ranging from 15 to 75 years. The three groups are group A (10-30 years), group B (31-60 years) and group C (61-90 years). From each group, 20 best prepared slides were taken for examination. The percentage volume of parenchyma (glandular portion) and stroma (fibrous part with blood vessels and fat) were estimated by the point counting technique with Zeiss-I integrating eyepiece under the light microscope at low magnification. The mean SD percentage volume of parenchyma varies 64.88 2.75 to 65.90 2.33 in group A, 56.40 12.57 to 59.10 3.87 in group B and 38.80 2.77 to 41.50 2.38 in group C. In contrast, the mean SD percentage volume of stroma varies 33.50 2.27 to 34.88 2.95 in group A, 40.30 3.83 to 41.56 4.16 in group B and 58.50 2.38 to 61.20 2.77 in group C. The percentage volume of connective tissue stroma was found to increase with increasing age with simultaneous decrease in glandular parenchyma. DOI: http://dx.doi.org/10.3329/akmmcj.v5i1.18765 Anwer Khan Modern Medical College Journal Vol. 5, No. 1: January 2014, Pages 10-13